2019
DOI: 10.21315/jps2019.30.s1.5
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic/Natural Filler Composites: A Short Review

Abstract: Plastics have many benefits due to their light weight, cost effectiveness, durability and other advantages. They are used as agricultural films, packaging, disposal consumer items, health, construction, etc. However, most plastics are not degradable which cause serious environmental problem. Addition of natural fillers into thermoplastics not only reduce the cost of the thermoplastic/natural filler composites but also help in reducing the waste of non-degradable plastic composite materials in the environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…A review of natural fibre reinforced in polymer composite reported that the use of these fibres in non-degradable polymer matrix enhanced their thermal degradability from the TGA studies [ 44 , 45 ]. The previous result on PLA/chitosan and PLA/CNF biocomposites showed a similar thermal degradation trend [ 36 , 46 ].…”
Section: Resultssupporting
confidence: 62%
“…A review of natural fibre reinforced in polymer composite reported that the use of these fibres in non-degradable polymer matrix enhanced their thermal degradability from the TGA studies [ 44 , 45 ]. The previous result on PLA/chitosan and PLA/CNF biocomposites showed a similar thermal degradation trend [ 36 , 46 ].…”
Section: Resultssupporting
confidence: 62%
“…The need to identify a useful and degradable polymeric material fabricated from renewable resources prompted the large-scale fabrication of PLA. [51][52][53][54][55][56][57] PLA is a biobased product belonging to the aliphatic polyester family. [58][59][60][61][62][63] It has numerous favorable properties including its strength, stiffness, biocompatibility, thermo-plasticity, monomer renewability and good processability.…”
Section: Starch and Plasticizers Low Costmentioning
confidence: 99%
“…PC combined with cellulose produced highly improved composites (100% improvement) compared to neat PC [ 20 ]. Advantages of wood fibers include low cost, biodegradability, renewability, and low density, making wood–PC composites environmentally friendly [ 21 , 22 , 23 ]. Moreover, lignocellulosic fibers improved the biocomposites’ fire retardancy compared to neat polymer [ 24 ].…”
Section: Introductionmentioning
confidence: 99%